Normalization of Multifocal Acoustic Radiation Force Impulse Images - Nuria GONZÁLEZ-SALIDO; Jorge CAMACHO (Archives of Acoustics)
Imaging the tissue displacements caused by Acoustic Radiation Force Impulse (ARFI) provides qualitative tissue elasticity maps around the focus. To increase imaging range, multi-focus techniques combine several images obtained with different focal depths. Since the acoustic radiation force depends on focus depth, axial distance and steering angle, a normalization process is required before blending multi-focal ARFI images so that changes in the displayed displacements represent true tissue elasticity variations. This work analyzes the sources of displacement variability in multi-focal-zone ARFI and proposes a procedure to normalize and combine partial images. The proposal is based on the system focal configuration, transducer characteristics and global tissue parameters found by ultrasonic measurements. Performance of the proposed algorithm is experimentally evaluated with tissue mimicking phantoms.